Increased Occupational Exposure to Body Fluids in Healthcare Workers During the COVID-19 Pandemic: A Retrospective study from 2013 to 2022 - Karla A. Romero-Mora; María Gómez-Palacio-Schjetnan; Laura L. Jiménez-Sánchez; Claudia Alvarado-de la Barrera; Akio Murakami-Ogasawara; Samuel E. Schulz-Medina; Santiago Ávila-Ríos (Revista de Investigación Clínica)
Background: Healthcare workers (HCWs) are at risk of body fluids’ exposure. Objective: The objective of this study was to study the incidence of occupational body fluid exposures in HCW at a tertiary hospital and largest coronavirus disease 2019 (COVID-19) center in Mexico. Method: Data on sociodemographics, exposure factors, and vaccination status were collected from questionnaires of HCWs self-reporting exposures (January 2013-December 2022). Hepatitis B and C virus (HBV and HCV) and human immunodeficiency virus (HIV) serology data were retrieved from the laboratory platform. Descriptive statistics and variable associations were analyzed. Results: Four hundred and eighty-two exposures occurred, 311 in women (64.5%). Exposure incidence was 19.09/1000 person-years; 80% were percutaneous; and 20% were splashes. Median age of exposed HCWs was 21 years (standard deviation = 9.65). Nurses were the most exposed (n = 172, 35.6%), mainly in patients room (n = 223, 46%). About 40.5% of HCW had protective antibody titers to HBV surface antigen (anti-HBs). Self-reported vaccination status and protective anti-HBs titers had poor concordance (kappa = 0.02). One hundred and ninety-seven HCW required HIV postexposure prophylaxis (40.8%) with no seroconversions. Exposures were highest in 2020 (78 cases, p = 0.001 vs. all years). Conclusion: A high proportion of HCW lacked protective anti-HBs titers. Increased occupational exposures during the COVID-19 pandemic underline the need for standard precautions, HBV immunization, staff training, and post-exposure protocols to enhance pandemics preparedness. (REV INVEST CLIN. [AHEAD OF PRINT])